Pengaruh Penggunaan Media Pembelajaran Berbasis Video Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Biologi Kelas X SMA Negeri 5 Palu - Pangeran, Rasti; Bialangi, Mursito; Masrianih; Febriani, Vita Indri; Arsy, Rizka Fardha; Shamdas, Gamar Binti Non (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of the use of video-based learning media on student learning outcomes in Biology class X at SMA Negeri 5 Palu. The background of this study is based on the low student learning outcomes caused by the use of learning media that are still predominantly conventional, such as lectures and textbooks. The study used a quantitative approach with a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects consisted of 66 students, divided into an experimental class (X M1, 33 students) with video-based learning treatment, and a control class (X M2, 33 students) with conventional methods. The research instruments included a questionnaire to determine student responses and learning outcome tests in the form of pre-tests and post-tests. Data analysis was carried out through validity tests, reliability tests, swimmer tests, and non-parametric tests (Wilcoxon Signed Rank Test and Mann-Whitney U Test) with the help of SPSS. The results showed that both the experimental and control groups experienced an increase in learning outcomes from pre-test to post-test, but the experimental group obtained a higher average score with a significant difference (p < 0.001). The questionnaire reliability test produced a Cronbach's Alpha value of 0.826 which is included in the very reliable category. The Mann-Whitney test showed a mean rank of the experimental group of 50.00, higher than the control of 17.00. Thus, it can be concluded that the use of video-based learning media has a significant effect and is more effective than conventional methods in improving students' understanding of Virus material in Biology subjects.